In silico analysis of the structure of variable domains of mouse single-chain antibodies specific to the human recombinant interferon β1b - Flyak, A.I.; Pavlova, M.V.; Gilchuk, P.V. (Цитология и генетика, 2009)
In silico analysis of the DNA encoding singlechain Fv antibodies (ScFv) specific to the human recombinant interferon β1b and α2b (rhIFNβ1b, rhIFNα2b) has been carried out. The V, D and J-gene segments, the complementaritydetermining (CDR) and framework (FR) regions, n-nucleotides as well as mutation rates which take place during the affinity maturation of the examined sequences have been determined. For the panel of ScFv against rhIFNβ1b isolated from an immune combinatorial cDNA library uniqueness of the CDRH3 loop by the length and amino acid composition has been shown. Multiple alignments with the nearest homologies from the NCBI databases have revealed that the sequences of ScFv obtained are new.